Emerging Market Spreads : Then Versus Now - Yafeh, Yishay (IMF Working Papers; Working Paper ;, 2000)
This paper analyzes yield spreads on sovereign debt issued by emerging markets using modern data from the 1990s and newly-collected historical data on debt traded in London during 1870-1913, a previous 'golden era' for international capital market integration. Applying several empirical approaches, we show that the co-movement of spreads across emerging markets is higher today than it was in the historical sample. We also show that sharp changes in spreads today tend to be mostly related to global events, whereas country-specific events played a bigger role in 1870-1913. Although we find some evidence that economic fundamentals, too, co-move more strongly today than at that earlier time, our interpretation of the results is that today's investors pay less attention to country-specific events than their predecessors did in 1870-1913.